2020
DOI: 10.3390/ani10091560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex and Age on Nutritional Content in Wild Axis Deer (Axis axis Erx.) Meat

Abstract: The aim of this study is to examine the effect of sex and age on proximate chemical, fatty acid, amino acid and mineral content of axis deer (Axis axis Erx.) meat. Sixteen (n = 16) animals were hunt-harvested and assigned to groups according sex and age (sub-adult and adult). All analyses were made on m. longissimus thoracis sampled between the 9th and 13th ribs. Minor differences in nutritional composition of axis deer meat were found between analysed sex and age groups. Axis deer meat has a high protein (22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 38 publications
2
10
1
Order By: Relevance
“…In the present study, the fat content in brown bear meat was higher than that reported for other omnivores [ 4 , 5 , 6 , 7 ] and herbivore wild game species [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The fat content in meat is highly variable and influenced by many factors, especially diet [ 1 ].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the present study, the fat content in brown bear meat was higher than that reported for other omnivores [ 4 , 5 , 6 , 7 ] and herbivore wild game species [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The fat content in meat is highly variable and influenced by many factors, especially diet [ 1 ].…”
Section: Discussioncontrasting
confidence: 78%
“…There have been numerous studies on the meat quality of different game species harvested worldwide, like wild boar ( Sus scrofa ) [ 4 , 5 , 6 , 7 ], red deer ( Cervus elaphus ), fallow deer ( Dama dama ) [ 8 , 9 , 10 , 11 , 12 , 13 ], European mouflon ( Ovis aries musimon ) and axis deer ( Axis axis ) [ 14 , 15 ], impala ( Aepyceros melampus ) and springbok ( Antidorcas marsupialis ) [ 16 , 17 , 18 , 19 ], black bear ( Ursus americanus ) [ 20 ], and beaver ( Castor fiber ) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In red deer, the fodder consumed between spring and autumn has paramount importance in this regard. The abundance of forest vegetation and agricultural crops contributes to a richer fatty acid profile and a more pronounced aroma in the meat of free-living red deer [ 19 , 23 , 28 ]. In this period, the main deer fodder comprises dicotyledonous herbaceous plants, grasses, legumes, sedges, and rushes (up to 80%).…”
Section: Discussionmentioning
confidence: 99%
“…This number increased to 857 in 2021, with approximately 35,000 red deer reared on farms [ 26 ]. Many aspects have been addressed in investigations of the nutritional value and meat quality in free-living red deer [ 17 , 18 , 27 , 28 , 29 , 30 ], farmed deer [ 31 , 32 , 33 , 34 ], and both groups in comparative studies [ 23 ]. The effects of sex [ 17 , 18 , 23 , 28 , 34 ], age [ 27 , 28 ], diet [ 33 ], slaughter season [ 32 ], and country of origin [ 32 ], mainly on the fatty acid profile, were determined in these studies carried out on conventional farms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation